UPAYA UNIFEM DALAM MENANGANI DEVADASI DI THAILAND PERIODE 2008-2011 - LESTARIANA "; Yusnarida Eka Nismi (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2014)
Women and girls trafficking is a form of modern-day slavery, and become the second largest criminal industry in the world after drug trade. Human trafficking is a crime fueled by global poverty, inadequate education and opportunity, ethnic discrimination and societal inequity between men and women by the demand for cheap labor and cheap sex. It is a crime that transcends cultures, class, and geography. “Devadasi” on Thailand is one of the others. This research has goal to open knowledge about intervention of UNIFEM as international organization fund by UN. The focus of this research is strategy UNIFEM to make a different and bring a change for women status in Thailand related to the gender discrimination in Devadasi culture. This research uses International Organization theory which has been revealed by Peter J. Katzenstein, Robert Keohane and Stephen D. Krasner. This research is qualitative research which is used by library observation.The result of this research prove that implementation of the Sister City partnership of Bandung (Indonesia) with Braunschweig (Germany) is motivated by the existence of similiar characteristics and common interest, so it makes ideal pattern of cooperation (sensitive interdependence) which is build not only for cover or complete the lack of the city, but also for increase the city’s potential. This motivation is also creates long-term pattern and short positive impact for both city. As theory of Robert Keohane and Joseph Nye about Complex Interdependence.Keywords: Devadasi, UNIFEM, Women and Girls Trafficking.